Prosodic traits in speech produced by children with autism spectrum disorders – Perceptual and acoustic measurements. (March 2018) - Dahlgren, SvenOlof; Sandberg, Annika D; Strömbergsson, Sofia; Wenhov, Lena; Råstam, Maria; Nettelbladt, Ulrika
Background: Autism spectrum disorder has been associated with atypical voice characteristics and prosody. In the scientific literature, four different aspects of atypical speech production in autism spectrum disorder have been highlighted; voice quality together with the prosodic aspects pitch, duration and intensity. Studies of prosody in autism spectrum disorder have almost exclusively used perceptual methods. Recently, some studies have used acoustic analyses. In these studies, it has been pointed out that the acoustic differences found are not necessarily perceived as atypical by listeners, which is why it is important to let listeners evaluate perceptual correlates to acoustic findings. The aims of this study were to use both perceptual and acoustic analyses to study prosodic production in children with autism spectrum disorder and to examine if voice and speech characteristics could be used as clinical markers for autism spectrum disorder. Method: Eleven children within normal range of intelligence diagnosed with autism spectrum disorder and 11 children with typical development participated. Every child was recorded telling a story elicited with the expression, reception and recall of narrative instrument. Excerpts of one minute were extracted from the audio files creating the material underlying the perceptual ratings and in the acoustic analysis. An evaluation procedure, partly based on a standardized voice evaluation procedure developed for clinical practice in Sweden, was designed for the perceptual judgments and analysis. To capture critical prosodic variables, aspects of prosody based on characteristic features of Swedish prosody, prosodic features known to cause Swedish children with language impairment particular problems and current research of prosodic impairments in children with autism, were used as rating variables. The acoustic analysis was based on the four variables fundamental frequency ( fo ) average, fo range, fo variation and speech rate, together with the language production-related variable number of words per utterance. Results: In the acoustic analysis, no differences were found with regards to fo -related variables or speech rate. However, the children in the autism spectrum disorder-group produced significantly more words per utterance than the typically developing children. The perceptual analysis showed no differences between the groups. Only three children with autism spectrum disorder were correctly identified as such. The narrative ability of these children, according to scores on the narrative assessment profile, was poorer than that of the other eight children. They were also more atypical in fluency and in speech rate. Given the small sample, the results should be interpreted with caution. Conclusions and implications: The only difference in prosodic production discovered in the acoustic analysis, namely that children with autism spectrum disorder used more words per utterance than the children in the comparison group, was not detected in the perceptual assessment. This implies that it was not perceived as atypical by expert listeners. The results indicate difficulties in using voice and speech characteristics as markers of autism spectrum disorder in clinical settings. The correct identification of some of the children as having autism spectrum disorder or not also indicates that some children with autism spectrum disorder have a prosodic production sufficiently 'atypical' in combination with a limited ability to tell stories to be perceived.